Memanfaatkan Air Irisan Bawang Merah Untuk Meningkatkan Kualitas Perkecambahan Benih Buncis (Phaseolus Vulgaris) - Charles Septiawan Zebua (Jurnal Ilmu Pertanian dan Perikanan, 2025)
This study aims to determine the effect of shallot (Allium ascalonicum) sliced ​​water on the quality of bean (Phaseolus vulgaris) seed germination. The study was conducted with two treatments, namely seeds soaked in plain water (control) and seeds soaked in shallot sliced ​​water for 8 hours. The results showed that seeds soaked in shallot water had a better germination percentage, growth rate, and root and shoot length than the control. Shallot sliced ​​water has been proven to contain natural growth stimulants that can improve the quality of seed germination organically.